Evaluation of exercise hypertension in healthy young adults: an observational study - Chinara, Aurobinda; Purohit, Prasanta; Mahapatra, Bibhupada (International Journal of Research in Medical Sciences, 2019)
Background: The prevalence of hypertension is increasing globally as well as in Indian subcontinent. Exercise leads to an increase in the blood pressure especially systolic blood pressure. However, an increase in the diastolic blood pressure after exercise remarks for a risk of cardio-vascular disease. This study was undertaken to evaluate the exercise hypertension among the healthy young adults. Methods: This prospective study was undertaken in a tertiary health care facility. A total of 150 healthy students were finally included in this study for analysis. The study subjects were belonging to 18-22 years old of both genders. The blood pressure was measured by sphygmomanometer. Author used two stair equipment for exercise in which students are allowed to step-up and step down for 5 minutes without any rest. The statistical analyses were carried out by using Graph-Pad Instate. Results: The mean age of the students was 19.8±1.3 years and 92(61.33%) being males. The mean systolic blood pressure was 117.1±7.74 mmHg in resting condition which was significantly increased to 140.0±13.9 mm Hg after exercise (p<0.0001). In contrast, the diastolic blood pressure in resting condition was 78.3±7.89 mm Hg which was significantly reduced to 71.85±7.96 mm Hg after exercise (p<0.0001). The decrease in the diastolic blood pressure was inconsistence and 9 students had increased value after exercise which was found to be normal. Conclusions: Both systolic and diastolic blood pressure measured during resting condition and after exercise was significantly differs. These differences were found to be normal which remarks for a better cardio-logical status in healthy young students.